Políticas de avaliação na educação superior: a racionalidade neoliberal na definição de qualidade no Enade - Alex de Oliveira Fernandes (2022)
The objective of this research was to investigate the Brazilian National Student Performance Examination (Exame Nacional de Desempenho dos Estudantes — Enade), part of the National Higher Education Assessment System (Sistema Nacional de Avaliação da Educação Superior — Sinaes), aiming at apprehending and questioning the concept of quality established by this exam in the evaluation of undergraduate courses of Teaching Degree in History of public and private institutions. To this end, the methodological procedures of a qualitative approach were adopted, namely, bibliographic research, review of literature, including state of the art and documental research. The sociological and socio-historical approach of the evaluation proposed by Afonso and Dias Sobrinho and the critical studies on evaluation policies in Higher Education, adopted as theoretical references in this investigation, made it possible to understand the nexus between the choices of evaluation modalities prevailing in the Sinaes system from 2004 to 2020 and the neoliberal rationality of the competition identified by Foucault (2008) as a central feature of neoliberalism. The analyses produced made it possible to verify that, through these evaluation policies, the Brazilian Government has been acting in the diffusion of the neoliberal rationality of competition in Higher Education. It was found that the Sinaes moved away from the concept of social quality, from which it was originated, and came closer to the concept of market quality, by introducing and valuing product and performance indicators in the composition of the quality indicators of undergraduate courses. It was also verified that the summative and technical-bureaucratic dimension of evaluation, anchored in the positivist paradigm, identified in the Enade, offers limitations to assess knowledge, added value by these courses in student training and to define the quality of Higher Education. For the service of comparing and ranking courses in the logic of competition, Enade provides technical reports that seek to place undergraduate courses in relation to the results obtained nationally. Despite the limitations identified in the Enade, it was found that a significant part of the dissertations and theses research selected for this work reiterate the political and pedagogical conception of the exam, naturalizing its results without the necessary problematization. In this sense, new critical studies that seek to problematize the neoliberal conception of the world, of the Human Capital Theory, absorbed in the Pedagogical Competencies that have been legitimized in evaluation policies in Higher Education to the detriment of other approaches, become relevant.